The Relevance of Islamic Educational Thoughts of K.H. Ahmad Dahlan and K.H. Hasyim Asy’ari in the 4.0 Era - Hardika Saputra; Istiqomah Istiqomah; Mustoto Mustoto (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This article explores the integration of Islamic educational principles from K.H. Ahmad Dahlan and K.H. Hasyim Asy’ari into the context of the 4.0 Era, characterized by rapid technological advancements and digital transformation. It examines how these traditional educational concepts can be adapted to address the challenges and opportunities of modern education. By focusing on the principles advocated by these influential figures—such as the fusion of religious and general knowledge, character development, and the preservation of Islamic scholarly traditions—the study highlights their relevance and application in contemporary settings. The findings suggest that combining these principles with modern educational demands can provide a balanced framework that supports both technological proficiency and ethical grounding. This approach not only prepares students for the digital age but also ensures they remain connected to their cultural and spiritual heritage.